2021
DOI: 10.1007/s12185-020-03054-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impacts of the mutational spectrum in Japanese patients with primary myelofibrosis

Abstract: Patients with primary myelofibrosis (PMF) have a poorer prognosis than those with other subtypes of myeloproliferative neoplasms (MPNs). To investigate the relationship between gene mutations and the prognosis of Japanese PMF patients, we analyzed mutations in 72 regions located in 14 MPN-relevant genes (CSF3R,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…The mutations were detected from raw fastq data generated by the MiniSeq System as previously described. 3 The detected mutations obtained from a study that we previously reported. 3 All statistical analyses were performed using the R program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mutations were detected from raw fastq data generated by the MiniSeq System as previously described. 3 The detected mutations obtained from a study that we previously reported. 3 All statistical analyses were performed using the R program.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled sequencing libraries were prepared as previously described 3 . Briefly, gDNA fragmentation and subsequent indices ligation was performed using the QIAseq® FX DNA Library Core Kit and QIAseq® CDI Y‐Adapter Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ASXL1 mutation was associated with leukocytosis, systemic symptoms, and >1% peripheral primitive cells; the SRSF2 mutation was associated with older age and >1% peripheral primitive cells; and the EZH2 mutation was associated with >1% peripheral primitive cells. The frequency of >1 HMR mutation was increased in the high-risk group in several studies [25] [26], while the 5-year survival (OS) was significantly lower in the group of patients with HMR mutations compared to the group without HMR mutations, 47.5% and 85%, respectively [25]. In a previous long-term prognostic study of 1282 PMF patients, early mortality in PMF was found to be associated with genetic risk factors, while survival beyond 20 years could be predicted by clinical variables including age, sex, blood count, and symptoms [27].…”
Section: Impact Of Hmr Mutations On the Prognosis Of Pmfmentioning
confidence: 97%